The Influence of Professionalism, Work Discipline and Work Environment on Employee Performance - Akbar , Muhammad Aiza; Suyono, Joko; Suyono, Aldrin Arizona; Elisabeth, Damarsari Ratnasahara; Sukaris, Sukaris (Universitas Muhammadiyah Gresik, 2025)
The aim of this research is to analyze the influence of professionalism, work discipline and work environment on employee performance of Balai Pelatihan Vokasi Dan Productivitas Sidoarjo (Vocational and Productivity Training Center in Sidoarjo). The sample in this research was all 38 employees of Vocational and Productivity Training Center in Sidaorjo. The data collection technique uses a questionnaire, while the data analysis technique uses multiple linear regression. The research results prove that professionalism, work discipline and the work environment have a partial and simultaneous influence on employee performance of Vocational and Productivity Training Center in Sidoarjo. Among these three variables, professionalism is proven to have a dominant influence on employee performance of Vocational and Productivity Training Center in Sidoarjo.